Effects of acute temperature changes on the swimming abilities and oxygen consumption of Ptychobarbus kaznakovi from the Lancang River. (25th January 2019) - Ke, Senfan; Tu, Zhiying; Li, Zhimin; Zhao, Shoujiang; Liu, Defu; Shi, Xiaotao
Summary: Water temperature is known to be a particularly important environmental factor that affects fish swimming performance, but it is unknow how acute temperature changes affect the fish performance of Ptychobarbus kaznakovi . P. kaznakovi in the Lancang River have declined quickly in recent years, and this species was used to examine the effects of acute temperature changes on swimming abilities and oxygen consumption in a Brett‐type swimming tunnel respirometer. The standard metabolic rate (SMR) and routine metabolic rate (RMR) showed 216% and 134% increases, respectively, at 22°C (an acute increase from 17 to 22°C) compared to those at 12°C (an acute decrease from 17 to 12°C). Moreover, the RMR was approximately 1.7, 1.6 and 1.3 times the value of the SMR at 12°C, 17°C and 22°C, respectively. The critical swimming speed ( U crit ) of P. kaznakovi at 22°C was 5.45 ± 0.45BL/S, which was 45% higher than that at 12°C (3.77 ± 0.92BL/S). The oxygen consumption rates (MO2 ) reached their maximum values at swimming speeds near the U crit for all the temperature treatments. The maximum metabolic rate (MMR) values at 12°C, 17°C and 22°C were 274.53 ± 142.60 (mgO2 kg −1 hr −1 ), 412.85 ± 216.34 (mgO2 kg −1 hr −1 ) and 1, 095.73 ± 52.50 (mgO2 kg −1 hr −1 ), respectively. Moreover, there was a narrow aerobic scope at 12°C compared to that at 17°C and 22°C. The effect of acute temperature changes on the swimming abilities and oxygen consumption of P. kaznakovi indicated that water temperature changes caused by dam construction could directly affect energy consumption during the upstream migration of fish.